Determinants of the Intention to Use Mobile Banking Applications - Mayte ROJAS; Martin A. MAURICIO (Communications of International Proceedings, 2022)
This article examines how the hedonic and utilitarian benefits influences satisfaction and trust to generate intention to use in the context of mobile banking. The hypotheses were tested using a sample of 219 mobile banking users, through structural equation modeling with the PLS technique. The main results allowed to verify all the hypotheses raised and revealed that the both benefits generate satisfaction and trust, finally influencing the use of mobile banking.
Keywords: Mobile banking; hedonic benefits; utility benefits; Intention to use.